ChemInform Abstract: An Efficient One‐Pot Conversion of Boc‐Protected Adenines to N6‐Ureas. Issue 12 (March 2016) - Machicao, Paulo A.; Peterson, Matt A.; Schols, Dominique
Abstract: The reaction products are screened for antiproliferative activity against a panel consisting of L1210, CEM, and HeLa cells.